Distinct and redundant functions of cyclin E1 and cyclin E2 in development and cancer - Caldon, C Elizabeth (BioMed Central, 2010)
The highly conserved E-type cyclins are core components of the cell cycle machinery, facilitating the transition into S phase through activation of the cyclin dependent kinases, and assembly of pre-replication complexes on DNA. Cyclin E1 and cyclin E2 are assumed to be functionally redundant, as cyclin E1(-/- )E2(-/- )mice are embryonic lethal while cyclin E1(-/- )and E2(-/- )single knockout mice have primarily normal phenotypes. However more detailed studies of the functions and regulation of the E-cyclins have unveiled potential additional roles for these proteins, such as in endoreplication and meiosis, which are more closely associated with either cyclin E1 or cyclin E2. Moreover, expression of each E-cyclin can be independently regulated by distinct transcription factors and microRNAs, allowing for context-specific expression. Furthermore, cyclins E1 and E2 are frequently expressed independently of one another in human cancer, with unique associations to signatures of poor prognosis. These data imply an absence of co-regulation of cyclins E1 and E2 during tumorigenesis and possibly different contributions to cancer progression. This is supported by in vitro data identifying divergent regulation of the two genes, as well as potentially different roles in vivo.